1980
DOI: 10.1002/1097-4679(198001)36:1<283::aid-jclp2270360137>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Interaction effects of internal vs. external locus of control and directive vs. nondirective therapy: Fact or fiction?

Abstract: Examined critically studies that claim that internals are more successful in nondirective therapy and externals in directive therapy. Deficiencies in the design statistical analysis, and outcome measures employed in these studies led to the conclusion that only slim support exists currently for the interaction hypothesis. Rotter's (1975) discussion of common misunderstandings of the locus of control construct and misuses of the Internal‐External Locus of Control Scale provided one context within which to expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…They reported that clients in all groups showed a significant decrease in social anxiety, but produced no evidence to support the hypothesis of a greater decrease in anxiety for internals in the internally focused treatment (self-reinforcement) and for externals in the external treatment (systematic desensitization). A re-examination of Meinster's results by Messer & Meinster (1980) revealed, however, that a greater proportion of externals improved in systematic desensitization therapy compared to internals.…”
Section: Effect Of Matching Locus Of Control With Treatment On Therapmentioning
confidence: 94%
“…They reported that clients in all groups showed a significant decrease in social anxiety, but produced no evidence to support the hypothesis of a greater decrease in anxiety for internals in the internally focused treatment (self-reinforcement) and for externals in the external treatment (systematic desensitization). A re-examination of Meinster's results by Messer & Meinster (1980) revealed, however, that a greater proportion of externals improved in systematic desensitization therapy compared to internals.…”
Section: Effect Of Matching Locus Of Control With Treatment On Therapmentioning
confidence: 94%
“…Earlier studies of RL mainly investigated attitudes (Cedar & Levant, ; Dembo, Sweitzer, & Lauritzen, ), while techniques and individual differences have received less attention. Abramowitz, Abramowitz, Roback, and Jackson () reported that internally oriented persons prefer nondirective approaches; a subsequent study of locus of control and preference for directive vs. nondirective counselling (Messer & Meinster, ) also supported this interaction. A recent meta‐analysis of counsellor directiveness and client reactance (Beutler et al, ) reported that clients' trait‐like resistance, matched with counsellor directiveness, predicts treatment outcome.…”
Section: Introductionmentioning
confidence: 91%
“…Although the findings that internals in the SDT and externals in the LDW did not reduce stress more than those individuals not matched on the locus of control variable may appear at variance with some of the previous research, a recent review by Messer and Meinster (1980) provides an explanation for the equivocal results.…”
Section: Friedman Lehktr and Stevensmentioning
confidence: 54%